2023
DOI: 10.1021/acs.jpcc.3c01350
|View full text |Cite
|
Sign up to set email alerts
|

Heavy versus Light Lanthanide Selectivity for Graphene Oxide Films Is Concentration-Dependent

Abstract: Rare earths are important materials in various technologies such as catalysis and optoelectronics. Graphene oxide (GO) is a promising material for separation applications, including the isolation of lanthanides from complex mixtures. Previous works using fatty acid monolayers have demonstrated preferential heavy versus light lanthanide adsorption, which has been attributed to differences in lanthanide ion size. In this work, we used interfacial X-ray fluorescence measurements to reveal that GO thin films at th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…Our group also considered the impact of trivalent ion charge density on water arrangement near interfacial GO films. 97 SFG analysis of GO films created on dilute subphases of higher and lower charge density ions showed similar 3200 cm −1 and 3400 cm −1 band intensities. SFG studies of GO films on high concentration subphases show a decrease in water signal, consistent with ion adsorption, for both trivalent ions.…”
Section: Graphene Oxide Surfacesmentioning
confidence: 77%
See 1 more Smart Citation
“…Our group also considered the impact of trivalent ion charge density on water arrangement near interfacial GO films. 97 SFG analysis of GO films created on dilute subphases of higher and lower charge density ions showed similar 3200 cm −1 and 3400 cm −1 band intensities. SFG studies of GO films on high concentration subphases show a decrease in water signal, consistent with ion adsorption, for both trivalent ions.…”
Section: Graphene Oxide Surfacesmentioning
confidence: 77%
“…To understand the impact of the ion character on sorption, we studied ion adsorption to GO films as a function of ion charge density and subphase concentration. 97 At low subphase concentrations, XFNTR analysis showed similar adsorption of ions with different charge densities to GO films at the air–water interface. Indeed, XR revealed nearly identical film structures.…”
Section: Graphene Oxide Surfacesmentioning
confidence: 92%
“…For instance, recent studies have revealed an anomalous increase in Debye length for highly concentrated solutions . Other observations at charged interfaces, such as an apparent overcharging with rubidium, yttrium, neodymium, lutetium, and thiocyanate, indicate the need for a new understanding beyond classical mean field theories to model ion adsorption at interfaces. Specific ion effects, ion–ion interactions, ion–surfactant chemistry, interfacial ion speciation, and other factors need to be considered in these investigations.…”
Section: Discussionmentioning
confidence: 99%
“…However, this sharp transition is not observed under arachidic acid (AA) monolayers, which exhibit a smoother adsorption curve . SFG studies show that a new −OH band at ∼3100 cm –1 appears with trivalent ion adsorption to the AA films, suggesting partial dehydration of the metal ion. ,, Considering that MC simulations neglect the ion hydration, it is possible that the dominance of direct electrostatic interactions varies depending on the headgroup–ion interactions, leading to this discrepancy. XFNTR experiments of lanthanum and lutetium adsorption on graphene oxide films demonstrate that between 10 μM and 1 mM bulk concentrations, both ions adsorb equally .…”
Section: Interfaces In Liquid–liquid Extractionmentioning
confidence: 99%
See 1 more Smart Citation